A mathematical model of salinity control in a river with an effect of internal waves using two explicit finite difference methods - Othata, Pornpon; Pochai, Nopparat (My University, 2021)
—Salinity is related to the quantity of salt in rivers, and that salt can take several different forms. Salinity is determined by water evaporation to dryness, and form residual measuring. The total salt content in water can in influence the taste of water. Drinking water at levels of salinity greater than around 1.0 g/L is drastically and rapidly unpalatable. In this research, two models, the internal wave hydrodynamic model and the salinity dispersion model, are proposed. The internal waves hydrodynamic model provides salinity internal wave and salinity flow velocity. The salinity dispersion model provides the salinity level. A modified salinity control model is also used in a river with a barrage dam. The suggested model provides salinity control releasing fresh water from a barrage dam where the salinity level is not higher than the standard and does not waste too much fresh water. An explicit finite difference method which is unconditionally stable is used for approximating the degree of salinity from the proposed model under many conditions.
Keywords: Explicit Finite Difference Methods; Hydrodynamic model; Index Terms—Salinity Control; Internal Waves; Salinity dispersion model